The Effect of Tillage’s Types to the Growth and Production in the Various Upland Rice (Oryza sativa L.) Varieties on Sandy Lands - Hakiki, Kharisma Nur; Sumarsono, Sumarsono; Sutardi, Sutardi (Universitas Muhammadiyah Malang, 2023)
The result of the study shows that the tillage method has a real and significant effect (P<0, 05) on Upland rice growth and production. The inpago 8 variety without tillage was able to produce the highest dry weight and 1000 seeds. The highest grain production was in the partially tillage method. The inpago 10 variety in the partial tillage method was able to produce the highest number of grains per panicle, grains production, 1000 seeds weight and harvest index. However, in the partial tillage method, inpago 12 variety was able to produce the highest grains per panicle, grains production, 1000 seeds weight and harvest index while without tillage method produced the highest dry weight and the highest filled grains percentage.The study's findings indicate that the tillage method exerts a substantial and statistically significant impact (P<0.05) on the growth and yield of upland rice. Specifically, the inpago 8 variety demonstrated the highest dry weight and 1000-seed count when cultivated without tillage. Furthermore, the partially tilled method resulted in the highest grain production. Within the partially tilled method, the inpago 10 variety exhibited superior performance in terms of grains per panicle, overall grain production, 1000-seed weight, and harvest index. Conversely, under the same partial tillage approach, the inpago 12 variety showcased notable superiority in grains per panicle, overall grain production, 1000-seed weight, and harvest index, while the untilled method yielded the highest dry weight and percentage of filled grains.